Enantioselective synthesis of (2R,3R)- and (2S,3S)-beta-hydroxyornithine - Pandey, Satyendra Kumar; Kumar, Pradeep (Tetrahedron Letters, 2006)
An efficient and short synthesis of (2R,3R)- and (2S,3S)-beta-hydroxyornithine 1a-b is described using Sharpless asymmetric dihydroxylation and regioselective nucleophilic opening of a cyclic sulfite as the key steps. (c) 2006 Elsevier Ltd. All rights reserved.

Efficient total synthesis of (-)-(3S,6R)-3,6-dihydroxy-10-methylundecanoic acid - Pandey, Satyendra Kumar; Kumar, Pradeep (European Journal of Organic Chemistry, 2007)
An efficient enantioselective synthesis of (-)-(3S,6R)-3,6-dihydroxy-10-methylundecanoic acid (1) from epichlorohydrin is described. The key steps include Jacobsen's HKR, Sharpless asymmetric dihydroxylation, regioselective opening of epoxide and cyclic sulfate. ((c) Wiley-VCH Verlag GmbH & Co. KGaA, 69451 Weinheim, Germany, 2007).
Keywords: cyclic sulfate; Dihydroxylation; Grignard reaction; hydroboration-oxidation; Jacobsen's hydrolytic kinetic resolution (HKR); regio selectivity

Enantioselective synthesis of (-)-pinellic acid - Naidu, S. Vasudeva; Kumar, Pradeep (Tetrahedron Letter, 2007)
An enantioselective convergent approach toward the total synthesis of pinellic acid 1 from 1,9-nonanediol is described. The synthetic strategy features iterative Sharpless asymmetric dihydroxylation, Sonogashira coupling and Birch reduction. (c) 2007 Elsevier Ltd. All rights reserved.

Efficient total synthesis of decarestrictine D - Guptali, Priti; Kumar, Pradeep (European Journal of Organic Chemistry, 2008)
An efficient total synthesis of decarestrictine D has been achieved using cross-metathesis or ring-closing metathesis and Yamaguchi macrolactonization as key steps. The stereogenic centres were generated by means of hydrolytic kinetic resolution (HKR) and Sharpless asymmetric dihydroxylation (AD).
Keywords: Cross metathesis; Hydrolytic kinetic resolution; Macrolides; Ring-closing metathesis; sharpless asymmetric dihydroxylation

Enantioselective hydrogenation of olefins by chiral iridium phosphorothioite complex covalently anchored on mesoporous silica - Sahoo, Suman; Kumar, Pradeep; Lefebvre, F.; Halligudi, Shivaraj B. (Journal of Catalysis, 2008)
Chiral monodentate phosphorous-based ligands have proven effective for the enantioselective hydrogenation of olefins. Binol-derived monodentate phosphorothioite (PS) ligand was synthesized from binol and thiopropyltriethoxysilane, and its iridium complex was covalently anchored to mesoporous silica supports like SBA-15, MCM-41, and MCM-48. These catalysts were characterized by different physicochemical techniques and assessed for their catalytic performances in the heterogeneous asymmetric hydrogenation of itaconic acid and its derivatives. It was found that the catalytic activities and enantioselectivities of the heterogenized iridium complex (IrPSSBA-15) in the hydrogenation reactions were comparable to its homogeneous analogue. Binol-derived monodentate phosphorothioite ligand in heterogeneously anchored form (iridium complex) is a more effective catalyst than the reported monodentate phosphorous ligand systems in the hydrogenation reactions, possibly due to the changes in electronic properties around the iridium metal center. The effects of substrate-to-catalyst molar ratio, solvents, and temperature on substrate conversions and enantioselectivities, of the products were investigated in hydrogenation reactions. (c) 2007 Elsevier Inc. All rights reserved.
Keywords: binol; Enantioselective hydrogenation; Immobilization; iridium complex; itaconic acid; Mesoporous silica SBA-15; monodentate ligand; phosphorothioite ligand

Enantioselective synthesis of decarestrictine J - Chowdhury, Partha Sarathi; Gupta, Priti; Kumar, Pradeep (Tetrahedron Letters, 2009)
An efficient total synthesis of decarestrictine J has been achieved using ring-closing metathesis and Yamaguchi esterification as key steps. The stereogenic centres were generated by means of iterative hydrolytic kinetic resolution (HKR) of racemic epoxides. (c) 2009 Elsevier Ltd. All rights reserved.
Keywords: Decanolides; epoxides; Hydrolytic kinetic resolution; Ring-closing metathesis; Yamaguchi esterification

Enantio- and diastereocontrolled total synthesis of (+)-strictifolione - Kumar, Pradeep; Pandey, Menaka; Gupta, Priti; Naidu, S. Vasudeva; Dhavale, Dilip D. (European Journal of Organic Chemistry, 2010)
A concise and practical enantioselective synthesis of (+)-strictifolione has been achieved in high diastereomeric excess using Jacobsen's hydrolytic kinetic resolution, proline-catalyzed sequential alpha-aminoxylation and Horner-Wadsworth-Emmons olefination of aldehyde and cross olefin/ring-closing metathesis as the key steps.
Keywords: Asymmetric synthesis; Hydrolytic kinetic resolution; lactones; Natural products; organocatalysis; Ring-closing metathesis; Total synthesis

Enantioselective synthesis of syn/anti-1,3-amino alcohols via proline-catalyzed sequential alpha-aminoxylation/alpha-amination and horner-wadsworth-emmons olefination of aldehydes - Jha, Vishwajeet; Kondekar, Nagendra B.; Kumar, Pradeep (Organic Letters, 2010)
A novel and general method for asymmetric synthesis of both syn/anti-1,3-amino alcohols is described. The method uses proline-catalyzed sequential alpha-aminoxylation/alpha-amination and Horner-Wadsworth-Emmons (HWE) olefination of aldehydes as the key step. By using this method, a short synthesis of a bioactive molecule, (R)-1-((S)-1-methylpyrrolidin-2-yl)-5-phenylpentan-2-ol, is also accomplished.

Enantio- and diastereocontrolled conversion of chiral epoxides to trans-cyclopropane carboxylates: application to the synthesis of cascarillic acid, grenadamide and L-(-)-CCG-II - Kumar, Pradeep; Dubey, Abhishek; Harbindu, Anand (Organic & Biomolecular Chemistry, 2012)
An efficient high yielding improved method for the enantio- and diastereoselective cyclopropanation of chiral epoxides using triethylphosphonoacetate and base (Wadsworth-Emmons cyclopropanation) is reported. The utility of this protocol is illustrated by concise and practical synthesis of cascarillic acid, grenadamide and L-(-)-CCG-II, a cyclopropane containing natural products.

Enantioselective modular total synthesis of macrolides Sch725674 and C-4-epi-Sch725674 - Sharma, Brijesh M.; Gontala, Arjun; Kumar, Pradeep (European Journal of Organic Chemistry, 2016)
The convergent total synthesis of Sch725674 has been accomplished by starting from (R)-1,2-epoxyheptane and assembling five modules in a highly stereoselective manner to give the final product in 6.6% overall yield. The same strategy was extended to the synthesis of its C-4 epimer. Key reactions of the synthetic pathway include a Jacobsen hydrolytic kinetic resolution of an epoxide followed by its regioselective opening through a Yamaguchi-Hirao alkynylation, and ring-closing metathesis reaction to furnish the unique 14-membered ring macrolactone. In addition, the influence of protecting groups on the efficiency of the ring-closing metathesis (RCM) macrocyclization has been studied to maximize its yields.
Keywords: Asymmetric synthesis; Hydrolytic kinetic resolution; Macrocycles; Metathesis; Natural products

Enantio- and diastereocontrolled conversion of chiral epoxides to trans-cyclopropane carboxylates: application to the synthesis of cascarillic acid, grenadamide and L-(-)-CCG-II (vol 10, pg 6987, 2012) - Kumar, Pradeep; Dubey, Abhishek; Harbindu, Anand (Organic & Biomolecular Chemistry, 2020)